Developing the leader within you - Maxwell, John C (New York Thomas Nelson, 2004)
Developing the Leader Within You is Dr. Maxwell?s first and most enduring leadership book, having sold more than one million copies. In this Christian Leaders Series edition of this Maxwell classic, you will discover the biblical foundation for leadership that John Maxwell has used as a pastor and business leader for more than forty years. These same principles and practices are available for everyday leaders in every walk of life. It is a lofty calling to lead a group?a family, a church, a nonprofi t, a business?and the timeless principles in this book will bring positive change in your life and in the lives of those around you. You will learn: The True Definition of Leader. ?Leadership is influence. That?s it. Nothing more; nothing less.? The Traits of Leadership. ?Leadership is not an exclusive club for those who were ?born with it.? The traits that are the raw materials of leadership can be acquired. Link them up with desire, and nothing can keep you from becoming a leader.? The Difference Between Management and Leadership. ?Making sure the work is done by others is the accomplishment of a manager. Inspiring others to do better work is the accomplishment of a leader.? God has called every believer to influence others, to be salt and light. Developing the Leader Within You will equip you to improve your leadership and inspire others.
Keywords: Leadership --Problems, exercise